Patch Test Results and Outcome in Patients with Complications from Total Knee Arthroplasty: A Consecutive Case Series - Sasseville, Denis; Alfalah, Khuzama; Savin, Evgeny (The Journal of Knee Surgery, 2019)
The role of hypersensitivity in implant-related complications remains controversial. The objectives of our study were to (1) establish the prevalence of hypersensitivity to components of knee prostheses in patients referred to our contact dermatitis clinic, (2) determine if patients with post-surgery dermatitis have become sensitized, and (3) describe the outcome of patients with and without hypersensitivity. We reviewed the charts of patients referred from 2007 to 2018 and extracted demographic information, date, type, and site of implant, clinical presentation, and results of patch testing (PT) or lymphocyte transformation tests (LTT). We called most patients to gather data such as clinical outcome, nature, and timing of additional surgery. Statistical analysis included computation of conventional descriptive statistics. Because of the type of study design, only some categorical variables were tested for possible associations by analytical tools (cross-tabulation). Thirty-nine patients, 23 men (59.0%), and 16 women (41.0%), were included. Their mean age in years was 63.3 (95% confidence interval [CI]: 60.9–65.7) ranging from 39.0 to 79.0, (standard deviation) = 9.69, without statistically significant differences between males and females. Five patients had positive PT possibly relevant to their implant. Four patients had revision surgery and two improved. Of nine patients with dermatitis, one with relevant PT did not improve after revision, and the dermatitis was unrelated to TKA in eight. Of the 26 patients without dermatitis or relevant PT results, 9 had revisions because of incapacitating symptoms, and 5 improved. Hypersensitivity to implant components is a potential factor in the etiology of TKA complications. Patients with confirmed hypersensitivity may benefit from revision. Our study, however, did not detect statistically significant differences in outcome of revision surgery between patients with positive versus negative PT or LTT. In spite of this, we consider that patients with a history suggestive of metal, acrylate or aminoglycoside allergy should be tested preoperatively to avoid hypersensitivity-related postoperative complications. In the absence of hypersensitivity, some patients with incapacitating symptoms may also improve following revision.
Keywords: total knee arthroplasty; hypersensitivity; patch testing; lymphocyte transformation test; revision